1981
DOI: 10.1039/p29810000193
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study of the mechanisms of S NAr reactions of neutral and cationic metal-complexed halogenoarenes with methoxide ion

Abstract: Rate studies have shown that the activation of halogenobenzenes towards nucleophilic attack by methoxide ion in methanol increases through theseriesof x-attached residues : (OC),Cr < (OC),Mo < (q5-CsH5)Fe+ < (OC),Mn+.For a given (x-arene) metal system, the reactivity of halogenoarene ligands towards methoxide decreases through the series: fluorobenzene > chlorobenzene chlorotoluene. Rates of reaction with methoxide are retarded in the presence of NaCIO, or LiCI, but accelerated when the methanol solvent is dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
7
1
Order By: Relevance
“…The advantage of using the CpFe' moiety is primarily due to the activating ability of this group towards displacement reactions. This was demonstrated clearly by the kinetic study carried out by Knipe et al (20,21). As well, the low toxicity and cost of this type of FeCp' complexation makes this route attractive in the synthesis of substituted aroof the cpFe+ complexes of chloroarenes in the synthesis of potentially biologically active molecules (2)(3)(4)(5).…”
Section: Introduction Matic Compounds Our Research Interest Is Focusmentioning
confidence: 66%
“…The advantage of using the CpFe' moiety is primarily due to the activating ability of this group towards displacement reactions. This was demonstrated clearly by the kinetic study carried out by Knipe et al (20,21). As well, the low toxicity and cost of this type of FeCp' complexation makes this route attractive in the synthesis of substituted aroof the cpFe+ complexes of chloroarenes in the synthesis of potentially biologically active molecules (2)(3)(4)(5).…”
Section: Introduction Matic Compounds Our Research Interest Is Focusmentioning
confidence: 66%
“…Treatment of 4 and 10 with PPh 3 gave 17 and 18 , respectively (Scheme ). Due to the high electrophilicities of (arene)Mn(CO) 3 + , PPh 3 selectively attacks the manganese carbonyls. When the PPh 3 -substituted chromium compounds [(η 6 -9,10-dihydroanthracene)Cr(CO) 2 PPh 3 ] ( 19 ) and [(η 6 - trans -stilbene)Cr(CO) 2 PPh 3 ] ( 20 ) were reacted with (naphthalene)Mn(CO) 3 + , we only recovered the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies of aromatic nucleophilic substitution ("S N Ar") reactions of halogen-modified aromatics have typically observed that the different halogens yield a reactivity trend that is the opposite of that we observe. 59 Elucidation of a detailed mechanism for the surface reaction is complicated by the presence of multiple crystal faces and the many overlapping features due to surface −OH groups and modes of adsorbed water. Prior studies of TiO 2 surfaces have revealed spectra much like those depicted in Figure 5a and b, with the spectra varying considerably depending on the past history of the TiO 2 and subsequent treatments.…”
Section: ■ Discussionmentioning
confidence: 99%